Palm-based ECG holter monitor - Angeles, Jocris M. (2005)
In lieu with the IRC laboratory objective of engineering low-cost biomedical devices, the fourth installment of the Palm ECG project aims to implement a Palm-Based ECG Holter Monitor. A Holter monitor is an ambulatory electrocardiography machine that allows recording of ECG signals over long periods of time. Compared to a standard ECG system, Holter monitors allow monitoring of ECG signals away from the doctor and the hospital. This type of monitoring helps in the detection of heart conditions that has symptoms that occur on an irregular basis. ECG signals obtained from the body is subjected to analog signal conditioning circuits for DC blocking, noise removal and amplification. These signals are then fed to a Z8F6401 microcontroller for analog-to-digital conversion, peak detection and transmission to the PDA handled. The Palm PDA displays the signals and stores it. This stored data can be uploaded to a PC thru a HotSync where the signals can be displayed using the Paml ECG Plotter done in Visual Basic 6. To be able to store hours worth of data, a data compression algorithm called Template Residual Coding (TRC) is used. TRC uses a template wave for the other supplementary waves. To reconstruct the signal, the template wave, a flag that indicates whether the succeeding wave is representable by the template wave and shift points are stored. Percent root-mean-square difference was used to evaluate the supplementary wave. A value of 5% or less means that the waveform is representable by the template. All processes were done real-time.